2000
DOI: 10.1159/000007806
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-Mediated Alterations in Gastric Epithelial Apoptosis and Proliferation in a <i>Mastomys</i> Rodent Model of Gastric Neoplasia

Abstract: Background/Aims: Hypergastrinemia secondary to low acid secretion is associated with gastric carcinoid formation in Mastomys. We investigated the effect of gastrin on oxyntic epithelial apoptosis and proliferation in this model. Methods: Hypergastrinemia and mucosal hyperplasia were induced by irreversible H2 receptor blockade with loxtidine. Gastrin levels were normalised in some animals by 10 days’ loxtidine withdrawal. Serum gastrin was determined by radioimmunoassay, proliferative, enterochromaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…Gastrin is a critical trophic factor for the oxyntic mucosa both in humans and animals (27). An association between apoptosis and hypergastrinemia has been reported previously in a rodent (Mastomys) model using an H 2 receptor antagonist (28). Moreover, given the finding of accelerated parietal cell loss in INS-GAS mice, we considered the possibility that this was attributable to increased apoptosis, and we showed that the expression of G-gly led to significant protection against G-17-stimulated apoptosis.…”
Section: Glycine-extended Gastrin and Atrophy In Mouse Stomachmentioning
confidence: 75%
“…Gastrin is a critical trophic factor for the oxyntic mucosa both in humans and animals (27). An association between apoptosis and hypergastrinemia has been reported previously in a rodent (Mastomys) model using an H 2 receptor antagonist (28). Moreover, given the finding of accelerated parietal cell loss in INS-GAS mice, we considered the possibility that this was attributable to increased apoptosis, and we showed that the expression of G-gly led to significant protection against G-17-stimulated apoptosis.…”
Section: Glycine-extended Gastrin and Atrophy In Mouse Stomachmentioning
confidence: 75%
“…However, the therapeutic use of loxtidine was advised against on the basis of the rodent studies (7,8). Due to its antisecretagogue effect, loxtidine has also been used for rapid induction of ECL cell carcinoids in Mastomys for studying growth regulation of the gastric mucosa (11)(12)(13)(14). In Mastomys, there is no difference between the sexes in gastrin concentration or subsequent carcinoid development after loxtidine administration.…”
Section: Introductionmentioning
confidence: 99%
“…The CCK-B/gastrin receptor is expressed in parietal and enterochromaffin-like (ECL) cells (4,38), and gastrin stimulates the secretory function as well as the production of these cell lineages (23,33,40). Elevated levels of serum gastrin induce expansion of parietal cell numbers in patients with gastrinoma (30).…”
mentioning
confidence: 99%